PERSPEKTIF PELANGGAN DAN PERSPEKTIF PEMBELAJARAN DAN PERTUMBUHAN DALAM MENGUKUR KINERJA INSTALASI FARMASI RUMAH SAKIT ADVENT MANADO DENGAN METODE BALANCED SCORECARD - Agow, Mikhael C.; Citraningtyas, Gayatri; Rumondor, Erladys M. (PHARMACON, 2021)
ABSTRACTPerformanced measurement used Balanced Scorecard with customer perspective and learn and growth perspective offers comprehensive solution to found how customers value products or services and how companies improved the resources of human quality become competent workers andÂ  able to produce excellent performance for the organization. This studied aims to determine the performance of Pharmacy Installation at Manado Advent Hospital based on the customer perspective and learning and growth perspective. The typed of research was non-experimental research with descriptive evaluative design. Data were obtained prospectively and retrospectively. The criteria of data were qualitative and quantitative. Qualitative data form an observation data and interviews. Quantitative data form questionnaire. The results customer perspective has 83.45% of patient satisfied to performanced of Pharmacy Installation at Manado Advent Hospital. Learning and growth perspective got results the employees has high satisfaction of job and spirit worked with value 3.05 and 3.06. The employee training of Pharmacy Installation at Manado Advent Hospital was never been implemented. The conclusions good performanced on patient satisfaction based on costumer perspective. Learn and growth perspective has good performance from work spirit and employee job satisfaction but poor performance that must be improved was employee trained.Keywords : Performance, Pharmacy Installation, Balanced Scorecard, Customer Perspective, Learning and Growth Perspective.ABSTRAKPengukuran kinerja menggunakan Balanced Scorecard dengan perspektif pelanggan dan perspektif pembelajaran dan pertumbuhan menawarkan solusi menyeluruh untuk mengetahui bagaimana pelanggan menilai produk atau jasa serta cara perusahaan meningkatkan kualitas sumber daya manusia untuk menjadi pekerja yang kompeten dan mampu menghasilkan kinerja yang prima bagi organisasi. Penelitian ini bertujuan untuk mengetahui kinerja Instalasi Farmasi Rumah Sakit Advent Manado berdasarkan perspektif pelanggan dan perspektif pertumbuhan dan pembelajaran. Penelitian ini merupakan jenis penelitian non eksperimental dengan rancangan deskriptif evaluatif. Data diperoleh secara prospektif dan retrospektif. Kriteria data berupa data kualitatif dan data kuantitatif. Data kualitatif berupa data observasi dan wawancara langsung. Data kuantitatif berupa kuesioner.Â  Hasil penelitian yang diperoleh yaitu kinerja perspektif pelanggan yaitu 83,45 % pasien menyatakan puas terhadap kinerja Instalasi Farmasi Rumah Sakit Advent Manado. Perspektif pembelajaran dan pertumbuhan memperoleh hasil karyawan memiliki semangat kerja dan kepuasan kerja yang tinggi yaitu 3,05 dan 3,06. Pelatihan karyawan Instalasi Rumah Sakit Advent Manado belum pernah dilakukan. Kesimpulan yang diperoleh yaitu kinerja yang baik pada kepuasan pasien, semangat kerja dan kepuasan kerja karyawan. Kinerja kurang baik yang harus diperbaiki yaitu pelatihan karyawan.Kata kunci : Kinerja, Instalasi Farmasi, Balanced Scorecard, Perspektif Pelanggan, Perspektif Pertumbuhan dan Pembelajaran